Istota „cywilizacji administracji publicznej” z perspektywy modyfikowalnego prawa administracyjnego - Dobosz, Piotr (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The subject matter of author’s considerations concerns the problems of public administration from a perspective of administrative law science and public administration science. In the paper the following issues have been indicated - for example – the tipping point of organizational efficiency of public administration, a notion of public administration civilization and modifying of administrative law. There are postulates after considerations with regard to a sphere of politics and legislation.
Keywords: the tipping point of organizational efficiency of public administration; modifying of administrative law; public administration civilization